The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41467-021-22296-9
|View full text |Cite
|
Sign up to set email alerts
|

On the limitations in assessing stability of oxygen evolution catalysts using aqueous model electrochemical cells

Abstract: Recent research indicates a severe discrepancy between oxygen evolution reaction catalysts dissolution in aqueous model systems and membrane electrode assemblies. This questions the relevance of the widespread aqueous testing for real world application. In this study, we aim to determine the processes responsible for the dissolution discrepancy. Experimental parameters known to diverge in both systems are individually tested for their influence on dissolution of an Ir-based catalyst. Ir dissolution is studied … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
133
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(155 citation statements)
references
References 61 publications
5
133
0
Order By: Relevance
“…Samples were tested at constant current in the chip EC-MS setup modified to collect electrolyte samples for ICP-MS measurements of metal dissolution before post-reaction LEIS characterization. The dissolution of OER catalysts is known to be dependent on the flow characteristics of the setup 32 – in this regard, the stagnant thin layer of electrolyte in the EC-MS setup resembles more the environment experienced by an OER catalyst in a PEMEC than do most aqueous model systems.…”
Section: Resultsmentioning
confidence: 99%
“…Samples were tested at constant current in the chip EC-MS setup modified to collect electrolyte samples for ICP-MS measurements of metal dissolution before post-reaction LEIS characterization. The dissolution of OER catalysts is known to be dependent on the flow characteristics of the setup 32 – in this regard, the stagnant thin layer of electrolyte in the EC-MS setup resembles more the environment experienced by an OER catalyst in a PEMEC than do most aqueous model systems.…”
Section: Resultsmentioning
confidence: 99%
“…Reproduced under the terms of the Creative Commons CC BY license. [ 60 ] Copyright 2021, The Authors, published by Springer Nature.…”
Section: Recent Mechanistic Studies On Ir‐based Oer Electrocatalystsmentioning
confidence: 99%
“…Later, Cherevko and co‐workers studied the dissolution of Ir‐based electrocatalysts using both aqueous electrochemical cells (AECs) and membrane electrode assemblies (MEAs) to explore the limitations of using the AEC model for evaluating the durability of OER electrocatalysts. [ 60 ] They compared the S‐number of IrO x electrocatalysts working under different conditions, and the results demonstrated that IrO x possesses a much larger S‐number under MEA conditions as compared with AECs (Figure 4c). Further, by varying the catalyst loading, the flow rates in SFCs, the concentration of dissolved Ir species, the Nafion content, and the pH of the working electrolyte, the authors discovered two major reasons for such differences.…”
Section: Recent Mechanistic Studies On Ir‐based Oer Electrocatalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…the reaction environment (ex. severe oxidation conditions under a high operation voltage) wherein even noble metals can be dissolved (1.5 ng cm -2 h -1 dissolution rate for Pt and 0.1 ng cm -2 h -1 dissolution rate for Ir) 12,13 . Thus, a key challenge is to develop highly corrosionresistant non-noble metal electrodes with the performance comparable to noble metal electrodes.…”
Section: Introductionmentioning
confidence: 99%